Inheritance of lethal gene ‘luteus-Pa’ from cacao progenies obtained by self and cross-fertilization (2017)
With the aim to study the inheritance of lethal gene ‘luteus-Pa’ in three derivated progenies from self and cross-fertilization of cacao (Theobroma cacao L) varieties, a study was carried out during January to September 2013. As genetic material C-25, S-5 y Pa-150 varieties were utilized and this one were self and cross pollinated and their progenies were divided in two replicates with 100 seeds each and sowed in plastic recipients containing a substrate 2:1(soil: sand). In order to contrast the observed segregation with its expected homologous 3:1 (monogenic inheritance), the Chi-square (X2) test was utilized. The results shown that only one from self-fertilized progeny of C-25 variety exhibited the mendelian segregation 3:1 in both replicates, so that it lead to infer this one is carrier of lethal gene ‘luteus-Pa’ in heterozygote condition whereas that the progeny from Pa-150 x C-25 cross no found none lethal seedling and submitted to Chi-square (X2) test it could be to infer this one no segregate in the proportion 3:1 therefore, the Pa-150 variety is no carrier of this lethal gene. A better comprehension on photobiological origin, supported by molecular markers and the functional genomics of this mutant can help to identify and understand the factors involve in the photosynthetic mechanisms.